Influence of extraction method on total phenolic content and antioxidant activity of Sappan Wood (Caesalpinia sappan L.) extract - Akmal, Tubagus; Tanjung, Yenni Puspita; Julianti, Andi Ika; Lestari, Aulia Gustiani; Aljan, Aljan (Universitas Mataram, 2024)
Sappan wood is a botanical species that contains a high concentration of phenolic compounds, which contribute to several pharmacological properties, including antidiabetic, antibacterial, antioxidant, and wound-healing activities. In order to achieve phenolic compounds of high quality and quantity, it is crucial to select an appropriate extraction procedure. Plant extraction is an important step for chemical isolation, chemical analysis, and evaluating the biological and pharmacological activities of plant compounds. Therefore, determining the most favorable extraction conditions is a critical undertaking in order to maximize both the quantity of active plant compounds and the extraction yield. This research aimed to compare extraction methods based on total phenolic content (TPC) and antioxidant activity (IC50). The extraction techniques employed include maceration, stirring-assisted extraction (SAE), ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE). The results show TPC values for maceration, SAE, UAE, and MAE, which are 132.85±1.44, 150.99±1.69, 206.70±6.56, and 115.70±1.44 mg GAE/g DE, respectively. The DPPH antioxidant activity (IC50) values are 32.33±2.64, 25.01±0.34, 20.68±0.29, and 29.18±0.70 µg/mL, respectively. The research findings indicate that various extraction procedures can impact the extraction yield, total phenolic content (TPC), and antioxidant activity (IC50) of sappan wood, and UAE is the best extraction method.